Clinical Application of Classic Prescription in Treating Alopecia - Guo, Youzhen; Jing, Huiling; Wang, Xingxing; Ren, Yu; Huang, Jiawen (Journal of Contemporary Medical Practice, 2024)
Zhang Zhongjing's works treatise on Febrile Diseases and synopsis of the Golden Chamber record many famous prescriptions. This paper has sorted out 6 famous prescriptions of rhubarb and Coptis purgative decoction, licorice purgative decoction, cassia twig plus dragon bone and oyster decoction, small bupleurum decoction, gegen decoction and Cassia Twig Fuling pill, and analyzed their dialectical thinking in the treatment of alopecia, to realize the subtleties of all sides and fully explore Zhongjing Fang, so as to provide new ideas for the clinical treatment of hair loss.